2018
DOI: 10.1002/ana.25196
|View full text |Cite
|
Sign up to set email alerts
|

Reduced contrast sensitivity among older women is associated with increased risk of cognitive impairment

Abstract: Among older women, reduced contrast sensitivity is associated with a greater risk of MCI/dementia. These findings suggest that visual system neurodegeneration or dysfunction may parallel or precede dementia-related cortical or subcortical degeneration, and that contrast sensitivity testing may be useful in identifying aging adults at high risk for dementia. Ann Neurol 2018;83:730-738.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 42 publications
3
48
2
Order By: Relevance
“…This finding is consistent with our previous results, which indicated that the integrity of the visual and sensorimotor networks is associated with the participants' general cognitive performance during healthy aging (Bagarinao et al, 2019). In a prospective study of older women, Ward et al (2018) have also demonstrated that participants with reduced visual function were associated with greater risk of dementia. Physical exercise has also been shown to help improved cognitive function through increased involvement of motorrelated networks (Ji et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with our previous results, which indicated that the integrity of the visual and sensorimotor networks is associated with the participants' general cognitive performance during healthy aging (Bagarinao et al, 2019). In a prospective study of older women, Ward et al (2018) have also demonstrated that participants with reduced visual function were associated with greater risk of dementia. Physical exercise has also been shown to help improved cognitive function through increased involvement of motorrelated networks (Ji et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Sensory impairments, including hearing, vision, and olfaction, affect up to 65% of older adults (1). Several prospective studies have found that sensory impairments are individually associated with increased risk of mortality (2,3) and dementia (4)(5)(6)(7)(8)(9)(10). Sensory impairment may be a marker of underlying neurodegeneration (6), or a consequence of the same disease processes as those affecting cognition, such as cerebrovascular disease (11)(12)(13).…”
mentioning
confidence: 99%
“…These deficits in MCI and subjective cognitive decline have been associated with increased amyloid and tau cortical deposition in temporal, parietal, and occipital lobes, and are significant predictors of amyloid and tau presence on imaging (Risacher et al, 2020). Since contrast sensitivity deficits have been shown to precede the clinical onset of dementia (Ward et al, 2018), these results suggest that contrast sensitivity may be a good biomarker of preclinical and early AD pathophysiology.…”
Section: Contrast Sensitivitymentioning
confidence: 92%